Determinants of immunization defaulters among children aged 12-23 months in Ambo town, Oromia, Ethiopia: A case-control study - Gurmessa Bekele; Jiregna Darega; Erimiyas Mulu; Menen Tsegaw (Taylor & Francis Group, 2024)
ABSTRACTImmunization is a public health intervention to reduce morbidity and mortality among children. However, vaccination becomes more effective if the child can receive the full course of recommended vaccination doses according to the schedule. Many children fail to complete the full course of vaccination. To identify the determinants of immunization defaulters among children aged 12-23 months in Ambo town, Oromia, Ethiopia. A community-based, unmatched, case-control study was done from October 1 to 25, 2021. A simple random sampling was used to select 317 (106 cases and 211 controls). Data were collected by using a pretested and structured questionnaire. Data were coded and entered to Epi-data version 3.1 and then transported to SPSS version 21.0 for statistical analysis. Descriptive analysis like frequency, mean, and percentage was calculated. Binary and multivariable logistic regression analysis was done. Finally, variables with a p value  < .05 were considered statistically significant. Urban residences (AOR = 0.288, 95% CI, 0.146, 570), government employee (AOR = 0.179, 95% CI, 0.057, 0.565), number of family members more than four (AOR = 2.696, 95% CI, 1.143, 6.358), higher income (AOR = 0.250, 95% CI, 0.099, 0.628), attending ANC (AOR = 0..237, 95% CI, 0.107, 0.525), and good awareness (AOR = 0.070, 95% CI, 0.005, 308) were significant predictors of immunization defaulters. This study has found that urban residences, government employee by occupation, number of family members more than four, higher monthly income, and attending ANC were identified as determinants of childhood immunization defaulters. Social Behavior Change intervention programs should focus on providing health information about the importance of the vaccine and vaccine schedule. Due attention should be given for rural residents and farmers who had limited access to information and are more prone to defaulting. Policy-makers should consider those identified factors while designing intervention programs to enhance vaccination coverage.